MANAJEMEN PERAWATAN LUKA PADA PASIEN DIABETES MELLITUS TIPE II DI RUMAH SAKIT WILAYAH JAKARTA TIMUR - Gusrina Komara Putri; Waluyo, Indah Apprillianti; Zaharany, Tsania Ayu (Indonesian Journal of Nursing Scientific, 2025)
Background: Type II DM is a chronic disease due to metabolic disorders which cause an increase in blood glucose levels. Diabetic ulcers are a complication of type II DM which occurs due to decreased peripheral circulation which is greatly influenced by high blood glucose levels and is closely related to peripheral arterial disease. Therefore, it is necessary to care for diabetic wounds and adhere to diet to avoid other complications. Research aim: The aim of this research is to apply nursing care to Type 2 DM patients with diabetic ulcers. Method: This research uses a descriptive analytical method with a case study approach which takes 2 patients with the same case. The research used a medical- surgical nursing care format including 5 nursing processes. Data collection techniques used include interviews, observation, physical examination and documentation studies. Results and discussion: After carrying out nursing actions in the form of wound care on Mr. After 3 x 24 hours the patient still complained of pain in the wound on the back when moving, the wound was still producing pus and the skin area around the wound was red and smelly. Leukocytes are still high at 15.12 10^3/uL. After carrying out nursing actions in the form of wound care on Mr. F, for 2x24 hours the patient still complained of pain in the leg wound when moving, there was no pus seepage but the skin around the wound looked reddish, dry, peeling. Leukocytes had decreased to 10.35 10^3/uL. Conclusion: The results of this case study concluded that the nurse's role is to recommend and teach diet, monitor blood sugar, exercise, take medication and care for wounds independently with diligent and routine check-ups with health services